Cell Cycle Arrest and Apoptosis in HT-29 Cells Induced by Dichloromethane Fraction From Toddalia asiatica (L.) Lam. - Xun Li; Xun Li; Zidong Qiu; Zidong Qiu; Qinghao Jin; Qinghao Jin; Guilin Chen; Guilin Chen; Mingquan Guo; Mingquan Guo (Frontiers Media S.A., 2018)
The roots of Toddalia asiatica (L.) Lam. (TA) has been often used in Chinese folk medicine to treat different diseases, including but not limited to arthritis, injuries, stomachache, and even tumors. However, the anti-cancer effects and the action mechanisms of TA remain elusive. Therefore, we firstly evaluated the effects of different extracts of TA on the growth of human colon cancer cells, and then tried to further elucidate their underlying molecular mechanisms. As a result, the dichloromethane fraction (DF) was found to possess the highest anti-proliferative activity with IC50 value at 18 μg/mL among all of the four extracts from TA, and strongly inhibited HT-29 cell growth and halted cell cycle progression in G2/M phase. DF also induced phosphatidylserine externalization and activated caspases -8, -9, and -3, suggesting DF induced apoptosis through intrinsic and extrinsic pathways. Furthermore, we found that HT-29 cell cycle arrest induced by DF could be the result of reactive oxygen species (ROS), as the ROS scavenger N-acetyl cysteine (NAC) attenuating it. Taken together, these results indicated that DF induced cell cycle arrest at G2/M phase and apoptosis in HT-29 cells, and could be a promising source for developing natural therapeutics for colon cancer.